Update of Laparoscopic Surgery in Borderline Ovarian Tumor: Systematic Review - Isabella Rotondella; Elisa Scarpelli; Giulia Martignon; Davide Scebba; Luciano Monfardini; Michela Gaiano; Alessandra De Finis; Martina Leotta; Carlotta Montrucchio; Asya Gallinelli; Stefano Cianci; Stefano Restaino; et al. (IMR Press, 2023)
Background: Borderline ovarian tumor (BOT) predominantly affects young women and is often diagnosed at an early stage. BOT accounts for 15% of all epithelial tumors. In this regard, a minimally invasive surgical approach and the ability to preserve fertility, without increasing the incidence of recurrences or worsening the prognosis, are crucial. This review aims to provide an update on the role and indications of laparoscopic surgery in BOTs. Methods: The electronic research was performed on Pubmed, Medline, and Embase. Articles published in the last 20 years (2004-2023) were included, and the following keywords were used: 'borderline ovarian tumor' and 'laparoscopic surgery', 'borderline ovarian tumor' and 'minimally invasive surgery', 'borderline ovarian tumor' and 'fertility sparing', 'borderline ovarian tumor' and 'recurrence' and 'Borderline ovarian tumor' and 'relapse'. The agreement about potential relevance was reached by consensus of the researchers and according to PRISMA statement guidelines. We thoroughly reviewed all bibliographies to assess the inclusion of any further eligible studies. We excluded studies that did not align with the study's objectives. Results: The electronic database search yielded 767 total studies. Of whom, 188 were published before 2004, 84 were case reports, and 45 were not in the English language. Of the remaining 450 studies, 148 were considered eligible for the study. We included 20 studies in this review. Conclusions: Despite the latest guidelines recommending an open approach for the treatment of BOT, the laparoscopic approach has gained popularity as a feasible and safe alternative. The use of an endo-bag, along with advanced laparoscopic skills, has made the minimally invasive approach increasingly safe, with oncological outcomes almost comparable to those of reference. Moreover, in the context of fertility-sparing surgery (FSS), laparoscopy seems to be associated with improved obstetrical outcomes, without detrimental effects on overall survival and disease-free survival. Therefore, the laparoscopic approach in the treatment of BOT appears to be a safe and effective option, especially in the case of FSS.